SUDDEN DEATH FROM VAGAL INHIBITION - Xhemali, Bledar; Ismaili, Zija; Matua, Linda; Cinije, Mirnela (European Scientific Journal, ESJ, 2013)
This paper will discuss and evaluate the alternative explanations of a sudden death due to the vagal inhibition caused from the application of a mild pressure to the neck. The death – not as a phenomenon, but as an „event“ caused by and related to several factors and circumstances – has a legal, medical and even social interest, whether its cause was natural or unnatural. The more unpredictably and faster a death occurs the more difficult the identification of its cause appears, especially in cases of trauma and of any present known or unknown, or even hidden, pathology. In this paper we will discuss a casus of a 27 year old male who died almost immediately after a pressure was applied to the neck. Necropsy examination showed some irregular light blue-red colored bruises on the neck region, which were caused by the fist. After the incision of the neck’s region, the bruises revealed a tissue crush and infiltrating hemorrhages involving all layers of the skin and the tissue.